Fitorremediação em lagoa facultativa de tratamento de efluente de queijaria: um estudo de caso utilizando macrófitas aquáticas - Rodrigues, Rebeca Gilvânia Silva (Universidade Federal de São Carlos, 2025)
The discharge of effluents without proper treatment is one of the main causes of pollution in water bodies, leading to a series of environmental problems that demand solutions combining environmental compliance and operational viability. In this context, bioremediation stands out as an alternative to optimize the efficiency of stabilization ponds in the dairy sector, aiming for a more sustainable, low-cost treatment with high pollutant removal capacity. This study evaluated the efficiency of phytoremediation using aquatic macrophytes in a facultative lagoon employed for the treatment of effluents from a processed dairy industry, located at the Savencia Brasil unit in Angatuba, São Paulo. The research aimed to verify the technical and environmental feasibility of applying the species Pontederia crassipes Mart., Canna x generalis, and Cyperus alternifolius L. to improve effluent quality and reduce organic load. The physicochemical and statistical monitoring of parameters such as pH, dissolved oxygen (DO), biochemical oxygen demand (BOD), and chemical oxygen demand (COD) demonstrated that the system performed satisfactorily, achieving an average BOD removal efficiency of 89.5% and COD removal above 80%, while maintaining pH levels within legal limits. The plant development of the root system and the high colonization capacity of the macrophytes favored the retention of suspended solids and stimulated microbial activity, enhancing effluent quality improvement. Seasonal variations and occasional operational interferences, such as breakage of containment areas and replanting periods, temporarily influenced performance but did not compromise treatment stability. The results demonstrated the potential of phytoremediation as a biological treatment model for dairy industry effluents. This technology represents an efficient, low-cost, and environmentally sustainable alternative, contributing to effluent compliance with current legislation and promoting local ecological benefits.
Phytoremediation in a facultative pond for dairy effluent treatment: a case study using aquatic macrophytes
Keywords: Efluente de laticínios; Fitorremediação; Lagoa facultativa; Macrófitas aquáticas; Queijaria; Tratamento biológico; Aquatic macrophytes; Biological treatment; Dairy factory; Dairy effluent; Facultative lagoon; Phytoremediation; ENGENHARIAS::ENGENHARIA SANITARIA::TRATAMENTO DE AGUAS DE ABASTECIMENTO E RESIDUARIAS; 6. Água Potável e Saneamento